Analysis Of The Policies Of The Sijunjung Regency Department Of Tourism, Youth And Sport Regarding Sporting Participation And Achievement: Analisis Kebijakan Dinas Pariwisata Pemuda Dan Olahraga Kabupaten Sijunjung Terhadap Partisipasi Dan Prestasi Olahraga - Idris, Natasya; Idris, Natasya; Chaeroni, Ahmad; Gusril; Ilham (Jurnal IKEOR, 2026)
This study’s issue is gap between sports policy formulation and its implementation at the regional level, particularly in Sijunjung Regency. Although Department of Tourism, Youth, & Sports (Disparpora) of Sijunjung Regency has launched several strategic programs, community participation in sports and regional athletic achievements have not yet shown optimal results. This study aimed to identify the policies implemented by Disparpora, analyze the factors influencing sports participation, evaluate the effectiveness of the policy in improving athletic achievement, and formulate strategic recommendations for sports development in the region. Descriptive-qualitative approach used in this study. Research was located in Sijunjung Regency involving 12 informants consisting of Disparpora officials, KONI administrators, coaches, athletes, teachers, and community members. Researcher collected data by observation, interviews, also documentation. Validity of data tested using source & technique triangulation, with analysis for its data employed interactive model involving collecting, reducing, also displaying data with conclusion drawing. Study’s finding proved sports policies in Sijunjung Regency have been directed toward increasing participation and achievement through programs such as Gerakan Seribu Bola, One Village One Event, athlete incentives, and collaboration with sports organizations. However, application still far from optimal due to inadequate sports facilities, limited budgets, uneven access between urban and rural areas, and a lack of certified coaches. Therefore, stronger policy synergy, infrastructure improvement, and community-based sports development are needed to improve participation and achievement in a sustainable manner. Keywords: Public Policy, Disparpora, Sports Participation, Sports Achievement